INTELLECTUAL CAPITAL AND FINANCIAL PERFORMANCE: BANKS’ RISK AS THE MEDIATING VARIABLE - Anastasia Dian Cahyaningrum; Apriani Dorkas Rambu Atahau (Jurnal Manajemen dan Kewirausahaan, 2021)
This study seeks to investigate the impact of intellectual capital on banks’ financial performance with banks’ risks as the intervening variable. By using the purposive sampling technique, we selected 30 sample firms from publicly listed Indonesian banks in 2015–2017. This study generated the research data from banks’ financial statements in those years. We then analyzed our data by using the Partial Least Square. The results demonstrate that banks’ risks do not mediate the relationship between intellectual capital and banks’ financial performance. Meanwhile, intellectual capital negatively affects operational risk and market risk. In addition, credit risk negatively affects banks’ financial performance, and liquidity risk negatively affects banks’ financial performance. Lastly, intellectual capital does not affect banks’ financial performance.